Illegal Online Loan (Pinjol) in Indonesia: Ethical and Human Rights Perspectives - Mikea Manitra Ramalina Ranaivo (Recht Studiosum Law Review, 2024)
The objective of this research is to explore the pervasive issue of illegal online loan (Pinjol) in Indonesia, focusing on its implications on human rights and ethical standards. This research uses sociolegal research method combined with statutory, sociological and case study approach, using secondary data which are analysed qualitatively. Through an analysis of factors driving individuals towards illegal Pinjol, regulatory frameworks governing Pinjol transactions, and the alarming cases of human rights violations related to Pinjol, this research highlights the multifaceted nature of the problem. Drawing on insights from government initiatives, regulatory measures, and proposed solutions, this research underscores the importance of comprehensive strategies to address illegal Pinjol practices while protecting the rights and dignity of consumers. By advocating for public awareness campaigns, enhanced consumer protection measures, community engagement, and strengthened legal frameworks, Indonesia can achieve a fair and transparent digital economy that prioritizes the well-being of all Indonesian citizens.